Potentials of marine natural products against malaria, leishmaniasis, and trypanosomiasis parasites: a review of recent articles - Justus Amuche Nweze; Florence N. Mbaoji; Yan-Ming Li; Li-Yan Yang; Shu-Shi Huang; Vincent N. Chigor; Emmanuel A. Eze; Li-Xia Pan; Ting Zhang; Deng-Feng Yang (Infectious Diseases of Poverty, 2021)
Abstract Background Malaria and neglected communicable protozoa parasitic diseases, such as leishmaniasis, and trypanosomiasis, are among the otherwise called diseases for neglected communities, which are habitual in underprivileged populations in developing tropical and subtropical regions of Africa, Asia, and the Americas. Some of the currently available therapeutic drugs have some limitations such as toxicity and questionable efficacy and long treatment period, which have encouraged resistance. These have prompted many researchers to focus on finding new drugs that are safe, effective, and affordable from marine environments. The aim of this review was to show the diversity, structural scaffolds, in-vitro or in-vivo efficacy, and recent progress made in the discovery/isolation of marine natural products (MNPs) with potent bioactivity against malaria, leishmaniasis, and trypanosomiasis. Main text We searched PubMed and Google scholar using Boolean Operators (AND, OR, and NOT) and the combination of related terms for articles on marine natural products (MNPs) discovery published only in English language from January 2016 to June 2020. Twenty nine articles reported the isolation, identification and antiparasitic activity of the isolated compounds from marine environment. A total of 125 compounds were reported to have been isolated, out of which 45 were newly isolated compounds. These compounds were all isolated from bacteria, a fungus, sponges, algae, a bryozoan, cnidarians and soft corals. In recent years, great progress is being made on anti-malarial drug discovery from marine organisms with the isolation of these potent compounds. Comparably, some of these promising antikinetoplastid MNPs have potency better or similar to conventional drugs and could be developed as both antileishmanial and antitrypanosomal drugs. However, very few of these MNPs have a pharmaceutical destiny due to lack of the following: sustainable production of the bioactive compounds, standard efficient screening methods, knowledge of the mechanism of action, partnerships between researchers and pharmaceutical industries. Conclusions It is crystal clear that marine organisms are a rich source of antiparasitic compounds, such as alkaloids, terpenoids, peptides, polyketides, terpene, coumarins, steroids, fatty acid derivatives, and lactones. The current and future technological innovation in natural products drug discovery will bolster the drug armamentarium for malaria and neglected tropical diseases.